Exploring Code Mixing: A Linguistic Case Study Of Tiktok Gen Z Beauty Influencer Communication - Jasmine Anindia Putri S; Cicilia Deandra Maya Putri (Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to identify the most dominant forms of code mixing used by Gen Z beauty influencers on the TikTok platform. The study employs a qualitative approach using a case study design focused on the beauty influencer @treezyneon, applying Muysken’s (2000) typology of code mixing, which categorizes code mixing into three types: insertion, alternation, and congruent lexicalization. The research data consists of utterances containing code-mixing elements obtained from 12 TikTok videos. The results indicate that the most dominant type of code-mixing is insertion, which appears most frequently compared to alternation, while congruent lexicalization was not found significantly in the data. The use of code mixing in the form of insertion is considered more flexible, practical, and in line with Gen Z’s digital communication style, which is fast-paced, expressive, and follows social media trends. This study demonstrates that the use of slang in code mixing serves not only as a stylistic device but also as part of Gen Z’s digital communication style, reflecting their closeness to global culture and social identity in digital media.